Designing a Posyandu Scheduling System using a Data-base to Improve Patient Service [Perancangan Sistem Penjadwalan Posyandu Menggunakan Basis Data untuk Meningkatkan Layanan Pasien] - Indra Astutik, Ika Ratna; Imanudin, Giri Fajar; Rosid, Mochamad Alfan; Aji, Sukma (Indonesian Journal Publisher, 2024)
Posyandu is a form of community-based health effort (UKBM) that is menaged and organized frm, by, and with the community in implementing healh development in order to empower the community and provide convenience to the obtaining basis heal/social service to accelerate the reduction in maternal and infant mortality. The Posyandu Scheduling System has a very important role to support the services of this public health program. Over time, problems arise regarding the system, in terms of preparing service schedules, still using the manual method, namely aliases, which are still handwritten to the recorder the Posyandu schedule in Kebonagung Village. This research is to design a website-based scheduling system that is useful for making it easier for cadres to disable and process Posyandu scheduling data in order to improve patient service. This system design uses the Hypertext Preprocessor (PHP) programming language, with a MySQL database, and uses Black Box testing to find out if the program is running as expected.